PERLINDUNGAN KONSUMEN TERHADAP PENYANDANG DISABILITAS SEBAGAI PENGGUNA JASA TRANS METRO PEKANBARU DI KOTA - Roberto Fernandes; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
As a business actor in public services in the field of transportation services, the Trans Metro Pekanbaru in its service has responsibility for the obligation to guarantee the rights of consumers using Trans Metro Pekanbaru. Considering Persons with Disabilities are consumers who are vulnerable groups, they should be given more protection with respect to their specificity, namely in Law of the Republic Indonesia Number 8 of 2016 Concerning Persons with Disabilities. In its implementation, Trans Metro Pekanbaru should perform their obligation in fulfilling the consumer right as stated in Law of the Republic Indonesia Number 8 of 1999 Concerning Consumer Protection. But in reality there has been a social deviation. Trans Metro Pekanbaru doesn’t provide special facilities for disabled persons as arranged. Based on Article 242 Act (1) of Law of the Republic Indonesia Number 22 of 2009 concerning Road Traffic and Transportation state that